Effects of medium- and long-term high-salinity environments on free amino acid content and related genes of Sinonovacula constricta - Zhu, Jie; Xu, Hongqiang; Zou, Zihao; Yao, Hanhan; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2024)
Introduction The razor clam, Sinonvacula constricta, one of the important mariculture bivalves in China, has unique flavor and wide salinity adaptability. The unique flavor mainly depends on the content of free amino acids and other umami substances in vivo. However, the flavor divergence of razor clam caused by the variable salinity breeding environment, while the mechanisms remain unclear. Methods Here, the razor clams were cultured in high salinity (30 ppt) and normal salinity (20 ppt) for eight weeks, and the effects of salinity on free amino acids and related genes expression in S. constricta were investigated by transcriptomics and metabolomics method. Results The results showed the free amino acid content under high salinity environment was significantly higher than normal salinity environment through the duration of the experiment (P < 0.05). The combination of transcriptomic and metabolomic data also indicated that high salinity environment resulted in enhanced metabolism of free amino acids. Furthermore, eight genes such as RALDH2, ACOX1, ALDH-E2 were potentially important for enhancing free amino acids metabolism under high salinity environment. Discussion This study preliminarily explained the regulation processes of high salinity environment on the metabolism of free amino acids in razor clams, providing a reference for the flavor regulation mechanism.